1976
DOI: 10.1677/joe.0.0710179
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Goitre in Sheep: Isolation of the Iodoproteins Which Replace Thyroglobulin

Abstract: Immunological and chromatographic studies of proteins from the congenital goitre of South Australian Merino sheep revealed that normal thyroglobulin is absent from the thyroid glands of these sheep. However, a thyroglobulin-immunoreactive iodoprotein was isolated by affinity chromatography on agarose gel to which antibody against thyroglobulin had been covalently bound. Sucrose-gradient ultracentrifugation indicated that this iodoprotein had a sedimentation coefficient of 8S and a molecular weight of approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The development of goiter in hypothyroidism may be due to a defect in thyroid hormone and thyroglobulin syntheses (Dolling & Good, 1976;Silva, Stantelices, Kishihara & Schneider, 1984;Ricketts, Pohl, de Martynoff et al 1985 ). However, it is also known that there is nongoitrous hypothyroidism which is unresponsive to TSH.…”
Section: Discussionmentioning
confidence: 99%
“…The development of goiter in hypothyroidism may be due to a defect in thyroid hormone and thyroglobulin syntheses (Dolling & Good, 1976;Silva, Stantelices, Kishihara & Schneider, 1984;Ricketts, Pohl, de Martynoff et al 1985 ). However, it is also known that there is nongoitrous hypothyroidism which is unresponsive to TSH.…”
Section: Discussionmentioning
confidence: 99%
“…Tg synthesis defects have been described not only in men, but also in cattle [167][168][169][170][171][172][173], goats [174][175][176][177], sheep [178][179][180][181][182][183], mouse [184][185][186], rats [187][188][189][190] and Bongo antelopes [191]. Hypothyroidism linked to Tg mutations have been reported in Afrikander cattle (p.R697X) [192][193][194][195], Dutch goats (p.Y296X) [196][197][198], cog/cog mouse (p.L2263P) [199] and rdw rats (p.G2300R) [200][201][202] (Table 4).…”
Section: Animal Thyroglobulin Gene Mutationsmentioning
confidence: 99%
“…Several thyroid disorders are known in man and animals in which the amount of Tg is reduced or in which abnormal Tg is found and often abnormal iodoproteins have been identified (Van Voorthuizen, 1978;. Until now three animal models of Tg disorders have been described in the literature: in cattle (Van Jaarsfeld et al, 1972;Sinadinovic et al, 1982), Merino sheep (Rac et al, 1968Falconer et al, 1970;Dolling & Good, 1975) and goats (De Vijlder et al, 1978;Van Voorthuizen, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been presented in the past (Van Voorthuizen, 1978) that Tg'is synthesized on large polysomes bound to the endoplasmic reticulum of the thyroid cell and then transported via the Golgi apparatus to the apical cell membrane where iodination of the tyrosil residues takes place . Several thyroid disorders have been reported in man (Michel et al, 1964;Mouriz et al, 1969;Andreoli et al, 1970;Lissitzky et al, 1973;Savoie et al, 1973;Riesco et al, 1974;Monaco et al, 1974;Wagar et al, 1976) and animals (Rae et al, 1968;Falconer er al., 1970;Van Jaarsveld et al, 1972;De Vijlder et al, 1978;Dolling et al, 1975;Sinadinovic et ul., 1982) in which the amount of thyroid Tg is reduced, absent or an abnormal Tg is found. Although the exact nature of the underlying defect in human beings remains unknown it was suggested that lack of Tg in congenital goitre is due to a defect in Tg messenger RNA which leads to aberrant processing and transport of Tg from its site of synthesis to the endoplasmic reticulum (Van Voorthuizen et al, 1978).…”
mentioning
confidence: 99%